1987
DOI: 10.1002/jbm.820210603
|View full text |Cite
|
Sign up to set email alerts
|

The influence of protein adsorption on interactions of cultured human endothelial cells with polymers

Abstract: A systematic study of the effects of polymer surface properties on the interaction with human endothelial cells (HEC) may lead to the development of small-diameter vascular grafts. HEC, suspended in culture medium containing 20% serum adhered and spread onto moderately wettable polymers such as TCPS (tissue culture polystyrene). Reduced or no adhesion of HEC was observed upon the hydrophobic polymers PETP (polyethyleneterephthalate, Dacron) and FEP (fluoroethylenepropylene copolymer, Teflon). Polymers precoate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
2
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 27 publications
6
91
2
1
Order By: Relevance
“…Fibronectin adsorption displays a maximum in adsorption at intermediate serum dilutions, a phenomenon similar to the maximum in fibrinogen adsorption at intermediate plasma dilutions (19,67). A corresponding maximum in cell spreading or attachment has been observed in several studies, using BHK cells (68), platelets (69), 3T3 cells (67), and endothelial cells (70). The magnitude and position of the peak in adsorption of fibronectin depends somewhat on the surface composition of the substrate (60).…”
Section: The Role Of Adsorbed Proteins In Cell Interactions With Solimentioning
confidence: 96%
“…Fibronectin adsorption displays a maximum in adsorption at intermediate serum dilutions, a phenomenon similar to the maximum in fibrinogen adsorption at intermediate plasma dilutions (19,67). A corresponding maximum in cell spreading or attachment has been observed in several studies, using BHK cells (68), platelets (69), 3T3 cells (67), and endothelial cells (70). The magnitude and position of the peak in adsorption of fibronectin depends somewhat on the surface composition of the substrate (60).…”
Section: The Role Of Adsorbed Proteins In Cell Interactions With Solimentioning
confidence: 96%
“…As a consequence, a decrease in the amount of a preadsorbed protein will not be detected if this amount is not very much reduced during exposure to the cell suspension [11]. By decreasing the serum concentration in the solutions used for pretreatment of the polymer surfaces, the amounts of adsorbed proteins are generally smaller [10]. Consequently, the endothelial cells had to be suspended in medium lacking serum to avoid adsorption of large amounts of serum proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, protein adsorption is one of the major determinants for adhesion and spreading of cells on polymers. Research on protein adsorption in our laboratory revealed that the amount of adsorbed fibronectin, a protein which promotes cell adhesion, from culture medium containing 20% human serum to TCPS is relatively small [10]. However, from this culture medium, relatively large amounts of highdensity lipoprotein, immunoglobulin G and human serum albumin (HSA), which all inhibit cell adhesion, adsorb to TCPS.…”
Section: © 1991 Chapman and Hallmentioning
confidence: 99%
See 2 more Smart Citations